IMMEDIATE RESPONSE GAIN IN HANDGRIP STRENGTH WITH ACUPUNCTURE: AN EXPERIMENTAL STUDY - Silvério-Lopes, Sandra; da Mota, Maria Paula Gonçalves (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Muscle strength is an important component for performing different daily tasks and has significant effect on health. Grip strength can be considered as one of the parameters of the overall strength state of the individuals. This study aimed to evaluate immediate response of the capacity to gain handgrip strength after the application of acupuncture. Materials and Methods: The study was experimental, quantitative, and partially blind clinical trial with a control group. Sample consisted in 73 healthy volunteers of both sexes, not athletes, with average age 35 ± 10.01 years, which were divided by deterministic allocation with sequential alternation in three groups: acupuncture (GACP n=24), sham acupuncture (Gsham n=25) and control (GCRT n=24). Calibrated mechanical manual dynamometer and needles 0.25 x 40mm were used. The handgrip test was performed in all groups, in both hands. Average measures were used for statistical analysis, a procedure done before and after the intervention. GACP received needles in TE5 (Waiguan), ST36 (Zusanli) and GB34 (Yanglingquan). The Gsham received superficial needles placed out of the acupoints. Results: GACP showed a significant strength gain of 4.78 Kgf (p = 0.005), Gsham showed a non-significant gain of 1.13 Kgf (p = 0.370) and GCRT that did not receive acupuncture intervention showed a non-significant reduction of handgrip strength average of about 1.97 Kgf (p = 0.210). Conclusion: Acupuncture in a single intervention was able to promote an immediate significant average gain strength response in handgrip of 4.78 Kgf